KEDUDUKAN WANITA DALAM PEMBAHAGIAN PUSAKA - Sulong, Jasni (Jurnal Syariah, 2019)
The status of women in inheritance has always been discussed by many writers. Many western writers have expressed astonishment that Islam recognizes property rights for women. They seem very much concern regarding the allocation of inheritance for Muslim women which they think is unfair compared to men:S' portion. In some Muslims communities, they do not follow this allocation due to the fact that for them Muslim women have been deprived of their property rights. Thus, this paper aims to elaborate the portion of Muslim women to their share in inheritance and the wisdom behind inequitable distribution among them as heirs.